A systematic review of YouTube videos on pain management during newborn blood tests. Issue 6 (December 2018) - Harrison, Denise; Modanloo, Shokoufeh; Desrosiers, Ashley; Poliquin, Louise; Bueno, Mariana; Reszel, Jessica; Sampson, Margaret
Abstract: This study aims to: (1) conduct a systematic review of YouTube videos showing newborn infants undergoing blood tests and (2) ascertain the use of recommended pain treatment strategies and infant pain during the filmed blood test. The pain was assessed using: (1) Neonatal Facial Coding System (NFCS) scores before, during and following the procedure; (2) Cry duration before and during the procedure. A total of 55 videos showing 63 procedures were included. Over half the babies cried and most babies scored the highest NFCS score of 4 at time of the poke as well as 15 s after the poke. YouTube videos of newborn infants undergoing blood sampling showed that recommended effective pain management interventions were rarely used and most infants were distressed during and following the procedure.